An Exploratory Discourse of the Operational Connection between Corporate Governance and Creative Accounting in Oil Company Administration in Nigeria - Ojo, Aderonke; Ohajionu, Uchechi; Ayo, Tosin (American Journal of Leadership and Governance, 2021)
This paper delves into and illuminates on the practices and successes of new and creative governance and accounting practices in Nigeria's oil and gas industry. The purpose of the paper is to find the nexus between corporate governance and creative accounting in Nigerian oil companies. It highlights various management concepts and facets of corporate governance in the Nigerian context that are immoral, but done in the interest of profit maximisation. The study also curiously documents how corporate governance affects the business model of Nigerian companies. This is mostly a doctrinal research that relies heavily on secondary data as obtained from available literature on creative accounting and corporate governance. Finally, there are several corporate governance procedures used in the oil and gas sector of Nigeria which often heavily reflects poorly on the efficiency of the firms, most notably the enforcement of criteria and metrics and their participation in decision-making. Often, the examination of calculation methods, their implementation, their outcomes, and their practical applications in the market environment. It is, without doubt, the reality that Nigerian companies, particularly those in the oil industry, are enmeshed in the practice. The paper finds that there is no guarantee those who are in charge of corporate governance who employ creative accounting will be able to do the best they can to create strategic and financial performance for Nigerian firms, most especially as better decisions are needed for stimulating the economy and recommends that ethical conduct, organizational transparency, accountability and probity be inculcated as an integral policy architecture for corporate governance in Nigeria's oil industry whilst advocating that the concept of separation of powers must be adopted to corporate governance if sustainability, lack of corporate impunity and a culture of unethical conduct in the boardroom would not be perpetually occasioned.